1996
DOI: 10.1055/s-2007-972801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Volume Resistive Exercise on Beta-Endorphin and Cortisol Concentrations

Abstract: It has been recently suggested that high and sustained lactate levels may elicit increases in peripheral B-EN concentrations (16). We have observed elevated and sustained lactate concentrations in response to a low-volume resistive exercise protocol (14) that were similar to those from other exercise protocols that produced elevated beta-endorphin (B-EN) concentrations. Thus, the purpose of the study was to determine the effects of a low-volume (21,700 J) resistive exercise repetition maximum (RM) protocol usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 2 publications
3
9
0
1
Order By: Relevance
“…As such, Wt tot increased with accumulating repetitions within each set and also varied across the three successive sets for a given exercise. A volume loading protocol at 65% 1-RM intensity was used because it has been shown to produce: (a) a wide range of Wt tot within and between exercise sets for both upper-and lower-body resistance exercises (2,13,17,27), and (b) large increases in blood [Hla] above resting levels during isotonic resistance exercise (1,7,8,13,17,27). Large response ranges for both Wt tot and [Hla] were requisite for correlational analyses of the type used to establish concurrent scale validity.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, Wt tot increased with accumulating repetitions within each set and also varied across the three successive sets for a given exercise. A volume loading protocol at 65% 1-RM intensity was used because it has been shown to produce: (a) a wide range of Wt tot within and between exercise sets for both upper-and lower-body resistance exercises (2,13,17,27), and (b) large increases in blood [Hla] above resting levels during isotonic resistance exercise (1,7,8,13,17,27). Large response ranges for both Wt tot and [Hla] were requisite for correlational analyses of the type used to establish concurrent scale validity.…”
Section: Experimental Designmentioning
confidence: 99%
“…R atings of perceived exertion (RPE) have been assessed for female and male subjects performing concentric and eccentric resistance exercise paradigms that varied the total volume of weight lifted (i.e., volume loading), percent of one repetition maximum muscular action (% 1-RM; i.e., intensity loading), and rest periods between separate sets and exercises (1,6 -8,14,17-19,26,27). These resistance exercise paradigms: (a) established force-effort psychophysical functions using torque, electromyography (EMG), and magnetic resonance imaging (MRI) as criterion measures (5,10,19,21); (b) examined blood lactic acid concentration ([Hla]), HR, EMG, epinephrine, norepinephrine, cortisol, betaendorphins, and pain as possible physiological mediators of the effort sense (1,4,7,8,11,13,(17)(18)(19)27,28); and (c) used RPE to prescribe muscular strength, endurance and hypertrophic training programs, and to track conditioning progress (1)(2)(3)9). In these foregoing investigations, RPE was assessed using the original and modified versions of Borg's 15-category scale and Borg's Category-Ratio (CR-10) scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the RPE during a multiple-set resistance exercise protocol has been poorly described. The few studies addressing this issue reported increases in RPE assets increased from moderate to high intensity (e.g., 80% of 10 repetition maximum [10RM], and 65% of 1RM) (12,13,22). In practice, these results suggest that a reduction in the intensity between sets is necessary to maintain the same RPE during multiple-set resistance training.…”
Section: Introductionmentioning
confidence: 99%
“…Em contraste, esses mesmos autores depois verificaram que os níveis de -end 1-31 diminuíam significativamente após a realização de um protocolo similar de exercício de força aplicado em estudantes (63). Outro estudo, em que sete homens treinados executaram um protocolo de três séries de 10 RM com quatro exercícios diferentes, demonstrou que um baixo volume de exercício de força não aumenta significativamente os níveis de -end (62). Por outro lado, Kraemer e cols.…”
Section: Respostas Da -End 1-31 Induzidas Pelo Exercício De Forçaunclassified